"The Last Missionary to Leave the Temple Should Turn off the Light": Sociological Remarks on the Decline of Japanese "Immigrant" Buddhism in Brazil - Usarski, Frank (Japanese journal of religious studies, 2008)
Empirical data indicate that the so-called "Buddhism of yellow color" that is predominantly associated with Japanese "immigrant" Buddhism, is constantly in decline in terms of "explicit" adherents. After some methodological observations, this article gives an overview of the relevant statistical data. The last part discusses possible reasons for these negative dynamics, referring to causes within Buddhist institutions, the ethnic community, and at the level of the individual.